2009
DOI: 10.1021/nl9017572
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Photoluminescence Behavior of CdSe/CdS Nanocrystals with Spherical, Linear, and Branched Topologies

Abstract: In recent years, a new generation of quantum confined colloidal semiconductor structures has emerged, with more complex shapes than simple quantum dots 1, 2 . These include nanorods 3 and tetrapods 4 . Beyond shape, it is also now possible to spatially vary the electron and hole potentials within these nanoparticles by varying the composition. Examples of these new structures include seeded dots, rods, and tetrapods, which contain a CdSe core embedded within a CdS shell [5][6][7][8] . These structures may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 30 publications
10
149
1
Order By: Relevance
“…The energy band structures of CdSe crystal under elastic strain effect have been widely investigated [26][27][28][29]. It has been demonstrated that compressive and tensile strains will result in wi dening and narrowing bandgap in CdSe crystal, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The energy band structures of CdSe crystal under elastic strain effect have been widely investigated [26][27][28][29]. It has been demonstrated that compressive and tensile strains will result in wi dening and narrowing bandgap in CdSe crystal, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4 Attaining such control at the nanoscale holds the promise of novel technological applications such as tunable photovoltaic devices, shock-absorbers, 7 and nanoscale stress sensors. 8,9 The additional surface effects also open the door to transformation pathways that are not available to the bulk material, potentially allowing a system to become trapped in metastable states with novel properties. [10][11][12] Moreover, sufficiently small nanocrystals can be synthesized with few or no defects and are thus ideal models to study the kinetics of solid-solid phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, backexchange of the Cu 2 Se/Cu 2 S structure could result in a strained CdSe/CdS interface, especially in the case of the larger seed, leading to a blue-shift in the recovered PL. 17,23 In addition, the 3.9-nm seed is exposed to the surface/ligand environment, making it sensitive to dielectric changes in the ligand shell and increase in surface traps resulting from the cation exchange process, 1 possibly …”
mentioning
confidence: 99%